2021
DOI: 10.21203/rs.3.rs-394978/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coexistence of dominant marine phytoplankton species sustained by nutrient specialization

Abstract: Prochlorococcus and Synechococcus are the two dominant picocyanobacteria in the low-nutrient surface waters of the subtropical ocean, but the basis for their coexistence in these biomes is still unclear. Here we combine in situ microcosm experiments and an ecological model to show that this coexistence can arise from specialization in the uptake of distinct nitrogen (N) substrates. In field incubations, the response of both Prochlorococcus and Synechococcus to nanomolar N amendments demonstrates N limitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Likewise, we found diel gene transcript abundances for phosphonate transporters with the heterotrophic bacterial order Rhodospiralles expressing phosphonate transporters in the morning (coinciding with phosphate transporters), Rhodobacter during the day, Prochlorococcus at dusk (coinciding with its phosphate transporters), and Synechococcus overnight (following its phosphate transporters). Our results suggest temporal partitioning of uptake for both phosphorus species, and coinciding timing of phosphate and phosphonate uptake on a taxon-by-taxon basis further suggests that substrate-level specialization is not necessarily sufficient to avoid competition for this scarce resource [25], and further suggests diel cycles in transporter gene transcription are not directly tied to changes in the relative pools of different phosphorus species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, we found diel gene transcript abundances for phosphonate transporters with the heterotrophic bacterial order Rhodospiralles expressing phosphonate transporters in the morning (coinciding with phosphate transporters), Rhodobacter during the day, Prochlorococcus at dusk (coinciding with its phosphate transporters), and Synechococcus overnight (following its phosphate transporters). Our results suggest temporal partitioning of uptake for both phosphorus species, and coinciding timing of phosphate and phosphonate uptake on a taxon-by-taxon basis further suggests that substrate-level specialization is not necessarily sufficient to avoid competition for this scarce resource [25], and further suggests diel cycles in transporter gene transcription are not directly tied to changes in the relative pools of different phosphorus species.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these results suggest temporal partitioning of uptake for both phosphorus species, and coinciding timing of phosphate and phosphonate uptake on a taxon-by-taxon basis further suggests that substrate-level specialization is not necessarily sufficient to avoid competition for this scarce resource [26], and further suggests diel cycles in transporter gene transcription are not directly tied to changes in the relative pools of different phosphorus species. Complementary evidence for diel temporal niche partitioning for distinct nutrients (N in the North Subtropical Pacific [28] and P in the Sargasso as shown here) may be indicative of complex, community-level metabolic plasticity across ocean basins.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in NH 4 in the water column corresponded to the only period when Prochlorococcus was found throughout the water column (Figure 7). It is generally observed that Prochlorococcus uses preferentially NH 4 for its N source and shows a limited ability to use nitrate (Masuda et al 2023). Surprisingly, DIP did not increase even in the December 2021 sampling immediately after Storm Carmel.…”
Section: Discussionmentioning
confidence: 99%